Susceptibility of Rhyzopertha dominica to high CO2 modified atmospheres in packaged chickpeas. (January 2020) - Iturralde-García, Rey D.; Wong-Corral, Francisco J.; Castañé, Cristina; Riudavets, Jordi
Abstract: Three MAs with 50%, 70% and 90% CO2 in air was tested at different exposure times on all the developmental stages of R. dominica using chickpeas packed with 4% and 96% filling ratio in which there was excess of CO2 . At 4% filling ratio the loss of the gas was negligible. The exposure time to reach 50% mortality (LT50 ) was estimated for each developmental stage and CO2 concentration, ranging from 7 h for larvae with 90% to 2 days for pupae with 50% CO2 . At 96% filling ratio and for the intervals of the estimated exposure times (LT50 ) from the 4% filling ratio, mortality decreased significantly for eggs and adults at the three MAs tested, while for the internal developmental stages, larvae at 50% and 70% CO2 and pupae in all concentrations of CO2, the susceptibility remained the same as with a 4% filling ratio. This decline in mortality of the external developmental stages was possible due to the sorption of CO2 by the chickpeas, which caused a loss of intergranular levels of CO2 between 17% and 29%. This sorption ranged from 0.1955 to 0.3285 g of CO2 per kg of chickpeas and produced a negative pressure of 77.12 to 60.65 kPa. In conclusion, when chickpeas are packed with high CO2 MAs, a decrease in the mortality of eggs and adults of R. dominica could be expected due to pulse sorption. Highlights: High filling ratios reduce CO2 content in package headspace due to sorption. Same larval and pupal mortality of R. dominica occurred at both filling ratios. Mortality of eggs and adults decreases at high filling ratios.